Search for flavor-changing neutral-current couplings between the top quark and the Z boson with proton-proton collisions at √s=13 TeV with the ATLAS detector - Aad, Georges; Baltes, Lisa Marie; Bartels, Falk; Castillo, Florencia Luciana; Czurylo, Marta; Dittmeier, Sebastian; Dunford, Monica; Franchino, Silvia; Klassen, Martin; Mkrtchyan, Tigran; Ott, Philipp; Rassloff, Damir Fabrice; et al. (Physical review, 2023)
A search for flavor-changing neutral-current couplings between a top quark, an up or charm quark, and a Z boson is presented, using proton-proton collision data at √s=13 TeV collected by the ATLAS detector at the Large Hadron Collider. The analyzed data set corresponds to an integrated luminosity of 139 fb−1. The search targets both single-top-quark events produced as gq→tZ (with q=u, c) and top-quark-pair events, with one top quark decaying through the t→Zq channel. The analysis considers events with three leptons (electrons or muons), a b-tagged jet, possible additional jets, and missing transverse momentum. The data are found to be consistent with the background-only hypothesis and 95% confidence-level limits on the t→Zq branching ratios, assuming only tensor operators of the Standard Model effective field theory framework contribute to the tZq vertices. These are 6.2×10−5 (13×10−5) for t→Zu (t→Zc) for a left-handed tZq coupling, and 6.6×10−5 (12×10−5) in the case of a right-handed coupling. These results are interpreted as 95% CL upper limits on the strength of the corresponding couplings, yielding limits for |C(13)*uW| and |C(13)*uB| (|C(31)uW| and |C(31)uB|) of 0.15 (0.16), and limits for |C(23)*uW| and |C(23)*uB| (|C(32)uW| and |C(32)uB|) of 0.22 (0.21), assuming a new-physics energy scale ΛNP of 1 TeV.